2002
DOI: 10.1074/jbc.m108073200
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Pancreatitis Caused by a Novel PRSS1 Mutation (Arg-122 → Cys) That Alters Autoactivation and Autodegradation of Cationic Trypsinogen

Abstract: Hereditary pancreatitis has been found to be associated with germline mutations in the cationic trypsinogen (PRSS1) gene. Here we report a family with hereditary pancreatitis that carries a novel PRSS1 mutation (R122C). This mutation cannot be diagnosed with the conventional screening method using AflIII restriction enzyme digest. We therefore propose a new assay based on restriction enzyme digest with BstUI, a technique that permits detection of the novel R122C mutation in addition to the most common R122H mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 33 publications
2
70
0
2
Order By: Relevance
“…Biochemical analysis of PRSS1 mutations revealed, for the two most common mutations, an increased trypsin activity. For the R122H mutation, increased trypsin activity is mediated by an increased stability, preventing physiologic autolysis, and for the N29I, mutation is related to enhanced trypsin auto-activation [31][32][33]. A similar clinical appearance is observed with SPINK1 mutations, which are also associated with hereditary chronic pancreatitis [34], even though the most frequently found N34S mutation does not influence anti-protease activity of SPINK1 [35].…”
Section: Influence Of Cigarette Smoke On Proteases and Anti-protease mentioning
confidence: 90%
“…Biochemical analysis of PRSS1 mutations revealed, for the two most common mutations, an increased trypsin activity. For the R122H mutation, increased trypsin activity is mediated by an increased stability, preventing physiologic autolysis, and for the N29I, mutation is related to enhanced trypsin auto-activation [31][32][33]. A similar clinical appearance is observed with SPINK1 mutations, which are also associated with hereditary chronic pancreatitis [34], even though the most frequently found N34S mutation does not influence anti-protease activity of SPINK1 [35].…”
Section: Influence Of Cigarette Smoke On Proteases and Anti-protease mentioning
confidence: 90%
“…A subsequent study, however, did not confirm this finding and demonstrated that activation of mutants N29I, N29T and R122H by cathepsin B is unaltered relative to wild-type trypsinogen [35]. Similarly, activation of mutants E79K, R122C or the double mutant N29I + N54S was unchanged [30,33,36]. Finally, experiments using synthetic analogs of the trypsinogen activation peptide revealed that activation of the D22G and K23R mutants by cathepsin B was actually decreased [37].…”
Section: Model #3 Cathepsin B Is a Pathological Trypsinogen Activatomentioning
confidence: 90%
“…The above notwithstanding, a loss of trypsin was also hypothesized to cause chronic pancreatitis, based upon the biochemical characterization of the R122C missense mutation. 17 However, as already pointed out by Teich et al, 8 no evidence exists to support this hypothesis from a genetic point of view, and clear 'loss of function' PRSS1 mutations (eg nonsense, splice site, or frameshift) have never been reported to cause the disease. In addition, although the E79K missense mutation was found to result in decreased autoactivation of cationic trypsinogen, E79K-trypsin proved to cause an increased transactivation of anionic trypsinogen.…”
Section: Introductionmentioning
confidence: 98%